Desain dan Analisis Quality of Service Pada Sistem Otomasi Rumah Menggunakan Wireless Sensor Network - Raharjo, Muhammad Agung; Ahmad, Andani; Wabula, Yuyun (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The problem raised in the study is how to control lights and air conditioners automatically via a smartphone with reliability and power efficiency. A home automation system for the use of lights and air conditioners works according to weather and temperature conditions using LDR sensors and DHT11 sensors from anywhere via the internet network so that it can identify and monitor the device in an on or off-state. For this reason, a design of a home control system is needed that can help users identify and monitor electronic devices remotely through a user interface, or automatically. This study aims to design a home automation system based on a Wireless Sensor Network (WSN) so that it can be used to control lights and air conditioners automatically and flexibly. In addition, this study also measures and analyzes Quality of Service (QoS) using delay parameters, packet loss, and throughput according to the TIPHON standard. From this study, the results of the tests carried out for the control function of electronic equipment connected to the home automation system using ESP8266, LDR, and Relay Node can function properly, while the network quality test according to the Quality of Service (QoS) Analysis using the TIPHON standard obtained results for Delay is 154.6 ms can be categorized as Good, while for the quality of the Loss packet it is 0.0033% with an outstanding category, while for the Throughput value is 2.2996 kbps which is categorized as bad.